2018
DOI: 10.1097/yct.0000000000000445
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation to the Right Temporoparietal Junction for Social Functioning in Autism Spectrum Disorder

Abstract: Anodal tDCS to the rTPJ may represent an effective treatment for improving social functioning in ASD, with a larger clinical trial needed to validate this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…These symptoms primarily fell into the domains of social functioning and interpersonal skills and suggest that rTMS may have broader applications in other disorders that occupy similar symptom domains, such as BDD 71 . A recent case report found that transcranial direct current stimulation at the right temporoparietal junction in an 18-year-old patient with ASD also improved social functioning; these gains were maintained at 2 months and were also associated with a decrease in emotional lability 72 . Bilateral deep brain stimulation at the nucleus accumbens in a 14-year-old boy with ASD led to significant improvements in self-injurious behaviors and may have promise in related contexts 73 .…”
Section: Discussion and Future Directionsmentioning
confidence: 98%
“…These symptoms primarily fell into the domains of social functioning and interpersonal skills and suggest that rTMS may have broader applications in other disorders that occupy similar symptom domains, such as BDD 71 . A recent case report found that transcranial direct current stimulation at the right temporoparietal junction in an 18-year-old patient with ASD also improved social functioning; these gains were maintained at 2 months and were also associated with a decrease in emotional lability 72 . Bilateral deep brain stimulation at the nucleus accumbens in a 14-year-old boy with ASD led to significant improvements in self-injurious behaviors and may have promise in related contexts 73 .…”
Section: Discussion and Future Directionsmentioning
confidence: 98%
“…Eight studies exclusively utilized tDCS as the therapeutic tool [ 33 - 40 ], 23 studies utilized solely rTMS as the therapeutic tool [ 41 - 63 ], and one study used both rTMS and tDCS to evaluate their therapeutic effects on ASD [ 64 ]. Six of the included articles were case-reports [ 35 , 40 , 43 , 47 , 49 , 53 ], nine were non-controlled trials [ 36 , 37 , 41 , 46 , 55 , 57 , 61 , 62 , 64 ], and the remaining 17 were controlled trials [ 33 , 34 , 38 , 39 , 42 , 44 , 45 , 48 , 50 - 52 , 54 , 56 , 58 - 60 , 63 ]. Eleven of the controlled studies used a sham group as the control [ 33 , 34 , 38 , 39 , 42 , 48 , 50 - 52 , 54 , 63 ] and the remaining six compared neuromodulated patients with waitlist controls.…”
Section: Synthesized Findingsmentioning
confidence: 99%
“…Figure 1 shows a schematic overview of the study selection process. Eight studies exclusively utilized tDCS as the therapeutic tool [33][34][35][36][37][38][39][40], 23 studies utilized solely rTMS as the therapeutic tool , and one study used both rTMS and tDCS to evaluate their therapeutic effects on ASD [64]. Six of the included articles were case-reports [35,40,43,47,49,53], nine were non-controlled trials [36,37,41,46,55,57,61,62,64], and the remaining 17 were controlled trials [33,34,38,39,42,44,45,48,[50][51][52]54,56,[58][59][60]63].…”
Section: Synthesized Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…To target these multiple processes, the right temporoparietal junction (rTPJ) may be optimal for stimulation, because of the rTPJ's role as part of a large-scale neural network for social cognition (Kennedy & Adolphs, 2012). The rTPJ contributes lower-level processing of environmental sensoryperceptual stimuli, such as discriminating between self and others, as well as higher-level socialcognitive processing, such as perspective-taking, empathy, theory of mind (ToM; Decety & Lamm, 2007) emotion verbal fluency (Esse Wilson, Trumbo, et al, 2018), and social functioning (Esse Wilson, Quinn, et al, 2018). The rTPJ is also specifically associated with deficits in empathy and ToM in individuals with ASD (Lombardo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%